Ressocialização de apenados? A magnitude da aplicação do ensino no ambiente prisional - Picolotto, Patricia (2019)
Education is one way of providing social integration and knowledge, and this integration within the prison system is one of the best ways to ensure a decent future for prisoners when they acquire freedom. The objective of this study is to identify, within the 4th Penitentiary Region of the State of Rio Grande do Sul, the magnitude of the teaching application within the prison environment, as a mechanism for the re-socialization of the inmates. The research will deal with a qualitative approach, with some aspects of quantitative analysis. The quantitative approach occurred through a secondary data survey, while the qualitative approach was conducted through an exploratory research, characterized as a case study of the single type incorporated, and a structured interview. The academic relevance to this theme is through the enrichment of the theme in future studies and greater knowledge about the subject by the academic population. As for professional relevance, this research is based on the improvement of the existing Political-Pedagogical Plan, so that education is actually applied in the state prison context, thus reducing the bureaucracy and slowness that involves the creation, approval of the plan and subsequent implantation. Through the data collected, it was evidenced that the implementation of education, in some way, contributes to the re-socialization of prisoners from the 4th Prison Region.